Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper presents a comparative analysis of the macroeconomic adjustment in Chile, Colombia, and Peru to commodity terms-of-trade shocks. The study is done in two steps: (1) an analysis of the impulse responses of key macroeconomic variables to terms-of-trade shocks and (2) an event study of the adjustment to the recent decline in commodity prices. The experiences of these countries highlight the importance of flexible exchange rates to help with the adjustment to lower commodity prices, and staying vigilant in addressing depreciation pressures on inflation through tightening monetary policies. On the fiscal front, evidence shows that greater fiscal space, like that of Chile and Peru, gives more room for accommodating terms-of-trade shocks.